Solid State Fermentation Process for Polygalacturonase Production Using Tray Bioreactor - S.R. Alcantara; F.L.H. Silva (Chemical Engineering Transactions, 2012)
Polygalacturonase are pectinolytics enzymes that have technological, functional and biological applications in the food processing and plant-fungus interactions. These enzymes are in the group of most industrially applied, being pioneers in wines and fruit juices preparation. The aim of this work was polygalacturonase production by solid state fermentation process in a tray bioreactor, using cashew apple dry bagasse and Aspergillus niger CCT0916 microorganism. Utilizing a 22 factorial experimental design, it was observed the influence of temperature and substrate thickness on the response polygalacturonase activity, keeping constant the mass of moist substrate at 500 g during the experiments. The higher enzymatic activity predicted by the model (7 U/g), with 53 h of fermentation, was achieved under the conditions: moisture 50 %w.b, 106 spores/g inoculated spores concentration, 1.5 %(w/w) of ammonium sulphate as nitrogen source, 35 °C fermentation temperature and 20 mm substrate thickness. This model was significant with 95 % confidence. It was observed that between the factors, temperature is the variable that most influence the process.